Pengaruh Ukuran Partikel dan Laju Alir terhadap Penyerapan Ion Logam Pb2+ pada Kulit Langsat (Lansium Domesticum) - Hamid, Syafira Putri; Kurniawati, Desy (Lembaga Yasin AlSys, 2024)
The presence of heavy metals is quite a serious problem, considering that their numbers continue to increase. Efforts to handle it have been carried out using various methods. An effective and cheap method is the biosorption method. This research to determine the absorption capacity of langsat peel (Lansium domesticum) for the absorption of Pb2+ metal ions using a column method. The parameters studied to determine optimum conditions were biosorbent particle sizes with size variations of 106, 150, 250 and 425 μm and flow rates of 1.2, 3.4 mL/minute. The results showed that the biosorption of Pb2+ metal ions was influenced by the biosorbent particle size and flow rate. The optimum particle size of the biosorbent is 106 μm and a flow rate of 1 mL/minute, with an absorption capacity of 14.615 mg/g and 14.345 mg/g, respectively.